(untitled) (Third Sector Social Economic Review, 2018)
Organizational health can be explained as sustaining the life around the organization and developing the ability to survive and cope, which is constantly developing in the long run. Organizational justice means employees are at the point of perceiving justice at work. The aim of this research is to investigate the effect of organizational health on the perception of organizational injustice of nurses. In this context, the study was carried out with 417 nurses in Mersin City Hospital, Mersin University Health Research and Application Hospital and a private hospital. The aim of the research is to measure the effect of organization health on the perception of organizational injustice of nurses. The effect of organizational health on nurses’ perception of organizational injustice was tested by regression analysis. According to the results of the research the health of the organization effectt negatively to nurses’ perceptions of organizational injustice’s dimension of effective communication, material gains, promotion possibilities, task distribution, resource allocation, management attitude, favorability and it was seen that there was no effect on the dimension of gender discrimination. It is seen that the Mersin City Hospital has the lowest level, Mersin University Health Research and Practice Hospital and private hospital have almost low health level.